Development of Ludo Game as Learning Media in Circular Motion - Selviana Khodizah; Irwandani Irwandani; Idham Kholid (Jurnal Pembelajaran Fisika, 2019)
This research aims to develop a medium of learning physics ludo game of the subject of the circular motion. One of the problems of education is the lack of facilities and infrastructure, so that teachers are required creative in improving the quality of learning in class, such as developing learning media. One interesting learning media and boredom of students in learning activities that game-based learning, such as the application of instructional media ludo game.The method used is research and development are adopting from Borg and Gall which has been modified by Sugiyono of 10 stages to 7 stages. The collection of data used in this study a questionnaire given to subject matter experts, media specialists, classroom teachers and learners class X. The resulting data type is qualitative data and quantitative data to determine the feasibility of product research and development resulted in physics teaching media in the form of the game ludo valid to be used based on those ratings of validator penilaian82,2% gain material experts, media expert validator obtained 93.70% votes, ratings teachers gained 82.76% votes. Assessment test responses of participants trained in small groups obtain a percentage value of 86.69% and uiji field trials of each school (I) 84.50% (II) 81.12%, (III) of 82.67%, which means that the media can be accepted by learners. Keywords: games, Ludo, learning media, physics learning DOI: http://dx.doi.org/10.23960/jpf.v7.n1.201903